2022
DOI: 10.21037/gs-22-650
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and verification of a nomogram to predict tumor-specific mortality risk in triple-negative breast cancer: a competing risk model based on the SEER cohort study

Abstract: Background: Triple-negative breast cancer (TNBC) is the subtype of breast cancer with the worst prognosis, and traditional survival analysis methods are biased when predicting mortality. To predict the risk of death in patients with triple-negative breast cancer more precisely, a competing risk model was developed. Methods:The clinicopathological data of the TNBC patients from 2010 to 2015 were collected from the Surveillance, Epidemiology, and End Results (SEER) database. The data were assigned into a trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Radiotherapy, one of the classic adjuvant therapies, provides patients with surgery opportunities or tumor cleaning after surgery. Consistent with Li et al ’ s. study, we found that patients with adjuvant radiotherapy had a better prognosis than those who did not undergo radiotherapy ( 37 ). However, the results in 2 randomized trials conflicts with our study ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…Radiotherapy, one of the classic adjuvant therapies, provides patients with surgery opportunities or tumor cleaning after surgery. Consistent with Li et al ’ s. study, we found that patients with adjuvant radiotherapy had a better prognosis than those who did not undergo radiotherapy ( 37 ). However, the results in 2 randomized trials conflicts with our study ( 38 , 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…CSM calculated by the traditional survival analysis method is higher than that calculated by the competitive risk model. [ 12 ] In this study, we first identified the factors that may affect the prognosis of HER2 + breast cancer currently available in the SEER database using a competitive risk model. The results showed that age, race, tumor grade, clinical stage, T stage, surgery status, radiotherapy, chemotherapy, and regional nodes examined were independent risk factors for the clinical outcome of HER2 + breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer, especially triple-negative breast cancers (TNBC), has a high cell proliferation rate and is prone to recurrence [ 46 ]. Martinon et al discovered the inflammasome in 2002 to link inflammation, tumorigenesis, angiogenesis, and metastasis [ 47 ]. There are three components to the inflammasome complex: the sensor molecule, the adaptor protein, and the receptor (Fig.…”
Section: The Role Of Nlrp3 In Breast Cancermentioning
confidence: 99%
“…1 ). PLRs, ALRs, RLRs, CLRs, and proteins with tripartite motifs, such as pyrin (also known as marenostrin or TRIM20) are among the molecules involved in the inflammasome [ 47 ].…”
Section: The Role Of Nlrp3 In Breast Cancermentioning
confidence: 99%